PENERAPAN MODEL PEMBELAJARAN COURSE REVIEW HORAY UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 36 MERANGIN - Michel Donang Manok; Hidayati Rais; Awatif (Hira Institute, 2025)
This research is a Class Action Research. This study aims to improve the mathematics learning outcomes of grade VIII students of SMP Negeri 36 Merangin through the Course Review Horay learning model. The subject of this study is grade VIII students of SMP Negeri 36 Merangin in the even semester of the 2023/2024 Academic Year. This research consists of two cycles, each of which consists of four stages, namely planning, implementation, observation and reflection. The data collection instruments of this study are student acrylic observation sheets and mathematics learning outcome tests. This action is said to be successful if the student manages to achieve KKM ≥70 and classical completeness of ≥75% during the mathematics learning outcome test cycle I and cycle II. From the observation of student learning activities, it can be seen that there is an improvement in the learning process from before and after the action of cycle I and cycle II. The results of this study showed that there was an increase in the percentage of students who reached the KKM from the percentage before the action was taken, which was 56.25%, increased to 68.75% in the first cycle of the learning outcome test, and increased to 81.25% in the second cycle. Based on the results of this study, it can be concluded that the application of the Course Review Horay learning model can improve the mathematics learning outcomes of grade VIII students of SMP Negeri 36 Merangin in the even semester of the 2023/2024 Academic Year.